Cloning and expression analysis of ZjHSP18.9 from Zoysia japonica. (21st February 2022) - Huang, Zhi‐yong; Sun, Xin‐bo; Zou, Yao
Abstract: The ZjHSP18.9 gene was isolated from Zoysia grass by homologous cloning based on publicly available transcriptome database. Sequence alignment analysis revealed that ZjHSP18.9 protein contains a classic Hsp23/ACD domain. Phylogenetic analysis and subcellular localization prediction suggested that ZjHSP18.9 belongs to cytosolic class VI subfamily. The expression profiles of ZjHSP18.9 in leaf and root after abiotic stress or Abscisic Acid (ABA) treatment was investigated using quantitative real‐time polymerase chain reaction. The results showed that the expression level of ZjHSP18.9 in leaf was higher than that in root. The expression of ZjHSP18.9 was strongly induced by high temperature in leaf; the ZjHSP18.9 expression level was up‐regulated in both leaf and root by the treatment of low temperature, salt and heavy metal, while down‐regulated under the treatment of drought and ABA. The gene expression profiles indicated that ZjHSP18.9 may play an important role in Zoysia grass response to environmental stress including extreme temperature, salinity, water deficiency and heavy metal through ABA dependent and/or independent pathway.